Meningkatakan Pengetahuan dan Keterampilan Perawat dalam Pemberian Asuhan Perkembangan melalui Pelatihan - Ayuda Nia Agustina; Yeni Rustina (Jurnal Persada Husada Indonesia, 2017)
Application of developmental care by nurses are essential to facilitate the growth and development of infants during care in the hospital, however not all nurses understand the benefits and practice of developmental care. This study identifies the influence of providing developmental care training using videos,booklets and practices. The study design used a quasi-experiment pre and post tests equivalent group involving 34 NICU nurses divided into 2 groups (control and intervention), chosen using total sampling method. Data were analyzed using SPSS software with dependent t-test. The results showed there is a significant difference in knowledge and skills between the intervention and control groups (p = 0.000), and there are no relationship between nurses’ characteristics (age, education, length of work, training history) against skills (p> 0.05).trained skills namely: nesting creation, families visitation facilities and positioning. Developmental care training for nurses is important to optimize developmental care application.